Respuesta :
Answer:
The step to take to avoid fraction is to solve for y in equation 2
Step-by-step explanation:
Given
-9x+ 4y =- 10
-9x+ 3y = 3
Required:
Step for solving using substitution (avoiding fraction)
Let -9x+ 4y =- 10 represent equation 1
and -9x+ 3y = 3 represent equation 2
The following points are to be noted
- Solving for x or y in equation 1 will definitely lead to having fractions
- Solving for x in equation 2 will also lead to having fractions
Having said that, the step to take to avoid fraction is to solve for y in equation 2
Check
[tex]-9x+ 3y = 3[/tex]
Add 9x to both sides
[tex]9x-9x+ 3y = 3 + 9x[/tex]
[tex]3y = 3 + 9x[/tex]
Divide through by 3
[tex]\frac{3y}{3} = \frac{3 + 9x}{3}[/tex]
[tex]y = \frac{3 + 9x}{3}[/tex]
Split fraction
[tex]y = \frac{3}{3} + \frac{9x}{3}[/tex]
[tex]y = 1 + 3x[/tex]
At the point, the expression of y can then be substituted in equation 1
Answer: solve for y in the second equation
Step-by-step explanation:
I got it right on edenuity